(untitled) - Jones, Leo (England, 2001)
This Audio CD set contains all the listening activities and materials featured in the Student's Book. A pocket-sized Personal Study Book is also available and offers useful reference material and fun practice activities to do out of class.
Keywords: Working in english,Làm việc bằng tiếng Anh,Anglais (langue),Tiếng Anh (ngôn ngữ); Langage commercial,Ngôn ngữ thương mại